2023
DOI: 10.1002/asi.24770
|View full text |Cite
|
Sign up to set email alerts
|

Understanding user‐generated questions in social Q&A: A goal‐framing approach

Abstract: In social Q&A, user‐generated questions can be viewed as goal expressions shaping the responses. Several studies have identified askers' goals from questions. However, it remains unclear how questions set goals for responders. To fill this gap, this research applies goal‐framing theory. Goal‐frames influence responses by attracting responders' attention to different goals. Eight question cues are used to identify gain, hedonic and normative goal‐frames. A total of 14,599 posts are collected. To investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…To analyze question answerability, question cues are the linguistic characteristics for responders to identify the asker's needs (Banerjee, 2017; Chowdhury, 2003) and make decisions regarding whether to answer. Importantly, it was found that askers can utilize various question cues to specify goals (Wu et al, 2023): (1) cognitive cues include complexity and specificity that specify the cognitive goals for responders (Te'eni, 1990; Wu et al, 2022a); (2) emotional cues convey personal feelings (i.e., emotional expressiveness, self‐disclosure) (Fu et al, 2022; Kring et al, 1994; Shi et al, 2018); and (3) social cues refer to collaborative climate and politeness that stress on collective goals and support social interactions (Petrov et al, 2020; Wu et al, 2022b) (refer to Figure 1). However, the influences of question cues on responders' evaluations of question answerability are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze question answerability, question cues are the linguistic characteristics for responders to identify the asker's needs (Banerjee, 2017; Chowdhury, 2003) and make decisions regarding whether to answer. Importantly, it was found that askers can utilize various question cues to specify goals (Wu et al, 2023): (1) cognitive cues include complexity and specificity that specify the cognitive goals for responders (Te'eni, 1990; Wu et al, 2022a); (2) emotional cues convey personal feelings (i.e., emotional expressiveness, self‐disclosure) (Fu et al, 2022; Kring et al, 1994; Shi et al, 2018); and (3) social cues refer to collaborative climate and politeness that stress on collective goals and support social interactions (Petrov et al, 2020; Wu et al, 2022b) (refer to Figure 1). However, the influences of question cues on responders' evaluations of question answerability are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze question answerability, question cues are (Banerjee, 2017;Chowdhury, 2003) and make decisions regarding whether to answer. Importantly, it was found that askers can utilize various question cues to specify goals (Wu et al, 2023): (1) cognitive cues include complexity and specificity that specify the cognitive goals for responders ;…”
Section: Introductionmentioning
confidence: 99%